Gone (and spread) with the birds: Can chorotype analysis highlight the spread of West Nile virus within the Afro-Palaearctic flyway? - García-Carrasco, J.; Muñoz, A.; Olivero, J.; Figuerola, J.; Fa, J.E.; Real, R. (Elsevier, 2023)
West Nile virus (WNV) is a globally significant vector-borne disease that is primarily transmitted between birds and mosquitoes. Recently, there has been an increase in WNV in southern Europe, with new cases reported in more northern regions. Bird migration plays a crucial role in the introduction of WNV in distant areas. To better understand and address this complex issue, we adopted a One Health approach, integrating clinical, zoological, and ecological data. We analyzed the role of migratory birds in the Palaearctic-African region in the spread of WNV across Africa and Europe. We categorized bird species into breeding and wintering chorotypes based on their distribution during the breeding season in the Western Palaearctic and the wintering season in the Afrotropical region, respectively. By linking these chorotypes to the occurrence of WNV outbreaks in both continents throughout the annual bird migration cycle, we investigated the relationship between migratory patterns and virus spread. We demonstrate that WNV-risk areas are interconnected through the migration of birds. We identified a total of 61 species that potentially contribute to the intercontinental spread of the virus or its variants, as well as pinpointed high-risk areas for future outbreaks. This interdisciplinary approach, which considers the interconnectedness of animals, humans, and ecosystems, represents a pioneering effort to establish connections between zoonotic diseases across continents. The findings of our study can aid in anticipating the arrival of new WNV strains and predicting the occurrence of other re-emerging diseases. By incorporating various disciplines, we can enhance our understanding of these complex dynamics and provide valuable insights for proactive and comprehensive disease management strategies.